Figures of migration gender, kinship, and the politics of representation - Cruz, Resto S. I (Philippine Studies: Historical and Ethnographic Viewpoints)
This article examines differences in the discursive representations of male and female overseas Filipino workers. Men have less discursive visibility than females, but men are seen as responsible breadwinners, virile, and/or threatening socio-economic and international hierarchies, while women are contradictorily portrayed as heroines and bad mothers. These representations result from migration's tensions and contradictions with historically established gender and kinship norms. Because these norms are central to Philippine class and status hierarchies, elite and middle-class anxieties thus mediate migrants? representations. Further, the state and global political economy shape these representations. This examination compels a rethinking of Philippine migration flows as feminized.